(untitled) (Research, Society and Development, 2020)
Dentigerous cyst infection is a rare condition that can lead to life-threatening situations. A situation unusual is the development of osteomyelitis with proliferative periostitis from infection of this cyst, with only one possible case published in the literature. The purpose of this article is to relate a rare association of a dentigerous cyst with osteomyelitis and proliferative periostitis. An 11-year-old patient compared for dental care with infection from second molar pericoronitis, who reached the third molar germ and progressing to osteomyelitis with proliferative periostitis, thatwas treated under general anesthesia. Histological exam of the tissues removed during the surgery revealed infected dentigerous cyst and osteomyelitis with proliferative periostitis. After the surgery, the patient progressed satisfactorily with improvement of the clinical complaints. This condition, although rare, should be considered as a differential diagnosis of several stomatognathic system lesions.